2018
DOI: 10.5007/2175-8077.2018v20n52p109
|View full text |Cite
|
Sign up to set email alerts
|

Proposições acerca do Ensino de Empreendedorismo nas Instituições de Ensino Superior Brasileiras: uma Revisão Bibliográfica

Abstract: O objetivo geral do artigo é analisar, a partir da revisão de literatura, as proposições acerca do ensino de empreendedorismo nas IES brasileiras. Quanto aos métodos, o estudo, é: bibliográfico, exploratório e qualitativo. A pesquisa identificou, que para construção de uma educação empreendedora de qualidade é necessária a integração da sociedade (com as IES e as escolas), além dos programas de empreendedorismo focarem no (a): know-how, formação empreendedora, desenvolvimento de habilidades, abertura de negóci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Our results show that participating in junior enterprises influence both entrepreneurial profile and intention, but its influence on entrepreneurial profile is more considerable. This is an important contribution for demonstrating that junior companies are fulfilling their role in the professional development and training of associates for the labor market (whether on their own business or not), stimulating students’ entrepreneurial spirit (Almeida et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that participating in junior enterprises influence both entrepreneurial profile and intention, but its influence on entrepreneurial profile is more considerable. This is an important contribution for demonstrating that junior companies are fulfilling their role in the professional development and training of associates for the labor market (whether on their own business or not), stimulating students’ entrepreneurial spirit (Almeida et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As a pedagogical practice of entrepreneurship education, junior enterprises are a valid teaching strategy owing to its fomenting nature; besides stimulating students’ entrepreneurial spirit (Almeida et al , 2019). These practices endow students with “know-how,” so that their behavior corroborates the knowledge, skills and attitudes forming the entrepreneurial subject (Almeida et al , 2019; Rocha & Freitas, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this fashion, university support can foster entrepreneurship (Shi et al, 2020) through, for example, product creation (Almeida et al, 2019), university incubators (Ahmed et al, 2019;Trivedi, 2016), technology transformation and consultants (Rideout & Gray, 2013) and financial funds (Inácio Júnior et al, 2016). In consonance, Kraaijenbrink et al (2010) suggested that to understand the effect of university support on entrepreneurship, it was crucial to measure in which extent they could have an impact on students.…”
Section: The Support Of Universitiesmentioning
confidence: 99%
“…Estudiosos que contestam a concepção mercadológica e hegemônica do capital propõem a construção de um empreendedorismo mais emancipatório, ressaltando que ele perpassa várias áreas do conhecimento, incluindo a educação (Almeida, Cordeiro & Silva, 2018). Quando o empreendedorismo é analisado de maneira mais ampla e os seus aspectos-chave são levados em consideração, percebe-se que é possível trazer esse conceito para dentro do contexto escolar, resultando em que seja visto cada vez mais como estratégia de desenvolvimento social e de crescimento econômico (Barros & Gonzaga, 2018).…”
Section: Introductionunclassified